Characteristics of Osteoarthritis Patients at PKU Bantul Hospital in 2024 - Prisila, Elvina; Wijayanti Sukirto, Novi; Ilham Rahmatullah, Andika; Pirman Abdul Aziz, Adinda; Arrafi Pratama, Rheycado; Chairunnisa Ramadhani, Salsabila; Yuniasih, Dewi (Universitas Ahmad Dahlan, 2025)
Osteoarthritis (OA) is a degenerative joint disorder that commonly affects the elderly population, primarily resulting from the aging process and prolonged mechanical stress on articular cartilage. The risk of deceloping OA significantly increases between the ages of 30 and 65, with individuals over the age of 65 facing a tenfold higher risk. Common clinical manifestations include joint pain, stiffness, swelling, and reduced mobility, which can severely impact quality of life. This study aims to provide a comprehensive overview of the demographic and clinical characteristics of OA patients treated at PKU Bantul Hospital between January and December 2024. A cross-sectional design was employed, utilizing secondary data extracted from hospital’s medical records. A total of 579 OA patients were identified, with a predominant female population (419 individals, 41,1%). The vast majority received outpatient care (540 individuals, 93,3%). Radiological examinations were conducted in 462 patients (80%), with the knee joint being the most commonly affected site (369 cases, 64%). These findings highlight the high burden of OA among elderly females and underscore the importance of early diagnosis and effective management strategies, particularly for knee involvement, to prevent disease progression and improve patient outcomes.